All the devils are here the hidden history of the financial crisis - McLean, Bethany; Nocera, Joseph (New York Portfolio/Penguin, 2010)
This surprising narrative goes back more than twenty years to reveal, in rich, anecdotal detail, how Wall Street, the mortgage industry, and the government conspired to change the way Americans bought their homes, creating a perfect storm. The authors take us inside elusive institutions such as Goldman Sachs, AIG, and Fannie Mae, to reveal who changed the game and why.
Acquired through Health Policy Development Program (HPDP) research grant.
Keywords: Global Financial Crisis, 2008-2009.; Financial crises -- United States -- History -- 21st century; Mortgage-backed securities -- United States; Subprime mortgage loans -- United States